Religion/Theology: Comparative Analysis of Islamic Satan and Miltonic Satan in Paradise Lost 1667. - Khan, Aziz Ullah (MultiTech Publisher, 2023)
This research will analyze the same share of Christianity and Islam in the interested ground of John Milton's